A lotus-inspired 3D biomimetic design toward an advanced solar steam evaporator with ultrahigh efficiency and remarkable stability. Issue 4 (17th February 2022) - Zhang, Rong; Xiang, Bo; Wang, Yating; Tang, Shaochun; Meng, Xiangkang
Abstract : Inspired by the natural lotus, a solar interfacial evaporator with a novel 3D biomimetic architecture was developed, which exhibited an extremely high evaporation rate of 3.23 kg·m −2 ·h −1 and energy efficiency reaching 153.20% under 1-sun. Abstract : Developing advanced solar-driven interfacial evaporators with both ultrahigh energy efficiency and long-term tolerability is highly desired but still a great challenge. Herein, inspired by the natural lotus, we develop a high-performance solar interfacial evaporator with a novel 3D biomimetic architecture. The lotus-inspired biomimetic evaporator (LBE) combines three key components, including a large "leaf" having strong solar energy absorption ability, hydrophilic "stems" working as water transport channels, and lotus root-like porous "roots" with minimized heat loss for improved respiration. The photothermal part in the LBE, analogous to a lotus leaf, possesses Janus wettability with a hydrophobic side above and a hydrophilic side below, which is achieved by a scalable method of in situ inducing ZIF-67 nanocubes into an electrospun fiber film followed by pyrolysis. In particular, the top side has a unique hierarchical network structure consisting of long porous carbon nanofibers with internally dispersed metal oxide nanocrystals, leading to highly efficient solar absorption of 91.37%. The 3D-LBE exhibits an extremely high evaporation rate of 3.23 kg m −2 h −1 and energy efficiency reaching 153.20% under 1-sun, which exceeds the theoretical limit and is the highest recorded, to the best of our knowledge. Notably, the 3D-LBE also shows impressive pollutant removal capabilities assuring long-term interfacial evaporation stability. The high-performance LBE promises many applications, such as wastewater treatment, sea salt production, and metal recovery.